2018
DOI: 10.1038/s41419-017-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel ruthenium complex with xanthoxylin induces S-phase arrest and causes ERK1/2-mediated apoptosis in HepG2 cells through a p53-independent pathway

Abstract: Ruthenium-based compounds have gained great interest due to their potent cytotoxicity in cancer cells; however, much of their potential applications remain unexplored. In this paper, we report the synthesis of a novel ruthenium complex with xanthoxylin (RCX) and the investigation of its cellular and molecular action in human hepatocellular carcinoma HepG2 cells. We found that RCX exhibited a potent cytotoxic effect in a panel of cancer cell lines in monolayer cultures and in a 3D model of multicellular cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
5
26
0
Order By: Relevance
“…The design of metallodrug-based compounds is an interesting strategy in medicinal chemistry [24] , [25] , [26] , [27] , [28] , [29] , [30] . The most important metallodrug-based compounds are the platinum-based antineoplastic agents.…”
Section: Introductionmentioning
confidence: 99%
“…The design of metallodrug-based compounds is an interesting strategy in medicinal chemistry [24] , [25] , [26] , [27] , [28] , [29] , [30] . The most important metallodrug-based compounds are the platinum-based antineoplastic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Other ruthenium complexes have been previously reported as potent cytotoxic agents, including cyclometalated ruthenium β-carboline complexes, which were cytotoxic to lung, liver, breast, and cervical cancers [ 8 ]; piplartine-containing ruthenium complexes, which were cytotoxic to colon, tongue, liver, breast, skin, and hematological cancers [ 5 ]; a ruthenium complex with xanthoxylin, which was cytotoxic to colon, breast, liver, tongue, gastric, skin, and hematological cancers [ 9 ]; ruthenium imidazole complexes, which were cytotoxic to lung, liver, breast, and cervical cancers [ 19 ]; and, a ruthenium-based 5-fluorouracil complex, which had enhanced cytotoxicity to breast, colon, liver, tongue, skin, and hematological cancers [ 10 ]. The IC 50 values of these compounds are below 10 μM for most of the tested cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these complexes induce cytoprotective autophagy via the ROS-mediated extracellular signal–regulated kinase (ERK) signaling pathway, and the inhibition of autophagy could facilitate cell apoptosis [ 19 ]. The ruthenium complex with xanthoxylin induces S-phase arrest and causes ERK1/2-mediated apoptosis in HepG2 cells through a p53-independent pathway [ 9 ]. The ruthenium complexes with phenylterpyridine derivatives trigger death receptor-mediated apoptosis in A375 cells [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ruthenium complexes act on telomere DNA, some interfere with replication and transcription of DNA, and others inhibit related enzymes ( Kurzwernhart et al, 2012 ; Jain et al, 2018 ). Furthermore, ruthenium complexes can block the cell cycle ( Kou et al, 2012 ; Wang et al, 2016 ; De Carvalho et al, 2018 ) and induce the formation of DNA photocrosslinking products to prevent RNA polymerization enzymes or exonucleases from binding to DNA, thereby causing tumor cell apoptosis ( Le Gac et al, 2009 ; Rickling et al, 2010 ). Studies have found that some dinuclear and polynuclear Ru(II) polypyridyl complexes bind stably to the G-quadruplex (G4-DNA) structure of telomere DNA ( Hiyama et al, 1995 ; Ambrus et al, 2006 ), inhibiting telomerase activity and blocking the function of DNA replication, thus, preventing normal cells from developing into immortalized tumor cells ( Rajput et al, 2006 ; Shi et al, 2008 ).…”
Section: Antitumor Targets and Mechanisms Of Ruthenium Complexesmentioning
confidence: 99%